Cost analysis study of oral hypoglycemic agents available in Nepalese market - Shrestha, Binaya (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Diabetes Mellitus is one of the major causes of morbidity, mortality and needs lifelong treatment. There is a wide range of variation in the prices of antidiabetic drugs marketed in Nepal. Thus, a study was planned to find out price variations in the oral hypoglycemic drugs available singly and number of manufacturing companies for each, also to evaluate the difference in cost of different brands of same active drug by calculating percentage variation of cost. Methods: Cost of a particular drug being manufactured by different companies, in the same strength and dosage forms was obtained from the price list provided by the pharmaceutical companies in Nepal and Indian Drug Review September 2013. The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and percentage variation in price was calculated. Results: Percentage price variation of the commonly used drugs found was metformin (500mg) 171.42%, metformin (850mg) 128.42%, metformin (1000mg) 80%, pioglitazone (15mg) 150% pioglitazone (30mg) 188.89%, sitagliptin (50mg) 33.33%, sitagliptin (100mg) 40% acarbose (25mg) 39.58%, acarbose (50mg) 32.60%, gliclazide (80mg) 108%, gliclazide (40mg) 83.33%, glibenclamide (2.5mg) 87%, glibenclamide (5mg), 80%, glimiperide (1mg) 91.67%, glimiperide (2mg) 300%, glimiperide (3mg) 100%, glimiperide (4mg) 36.84%. Conclusion: The average percentage price variation of different brands of the same oral hypoglycemic drugs manufactured in Nepal is very wide. The appraisal and management of marketing drugs should be directed toward maximizing the benefits of therapy and minimizing negative personal and economic consequences.